Human resource planning on employee performance at a public broadcasting institution in South Sulawesi - Nurbaya, Sitti; Winanda, Nanda; Maklassa, Dg. (International Journal Labs, 2023)
This research is a quantitative research in nature with the aim of knowing the effect of human resource planning on employee performance at the TVRI South Sulawesi Public Broadcasting Institution (LPP). The data collection method used in this study was to distribute questionnaires to 62 respondents as the research sample. The data analysis technique used is descriptive statistical analysis, simple linear regression test, R test and t test using statistics through the application version of the Statistical Package for the Social Science (SPSS). 23.The results of this study indicate that Human Resource Planning has a positive and significant effect on Employee Performance at the TVRI South Sulawesi Public Broadcasting Institution (LPP).